IMPROVEMENT OF METHODS FOR DETERMINING THE EFFECTIVENESS OF RESOURCE POTENTIAL USE (Web of Teachers: Inderscience Research, 2026)
The article explores methods for improving the assessment of resource potential effectiveness in the road transport complex, with a focus on economic and social outcomes in the context of Uzbekistan's economy. It distinguishes between economic efficiency - measured as cost savings or relative indicators (e.g., sum/tkm) derived from income, transport performance, and proposed optimizations - and social efficiency, encompassing benefits such as improved occupational safety, environmental protection, and broader societal gains. The study proposes practical applications of developed economic models, methodologies, and management systems, predicting outcomes including reduced production costs across economic sectors, accelerated development of a competitive transport services market, substantial budget savings through public-private partnerships, and enhanced synergistic performance via coordinated intermodal transport management.